KEHIDUPAN NARAPIDANA PEREMPUAN DI CABANG RUTAN BAGANSIAPIAPI ROKAN HILIR - Mifthahus Sya’adah; Achmad Hidir (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2021)
life of female prisoners at the Rokan Hilir Bagansiapiapi Detention Center. This research was conducted in the city of Bagansiapiapi, Rokan Hilir Regency, precisely on Jalan Dr. Pratomo behind the Bagansiapiapi City Regional Hospital. The purpose of this research is done because they want to see the lives of female inmates in detention Branch Bagansiapiapi which at that Branch Rutan ketauhi are merged between prisoners and detainees both the male-male and female. In this study, researchers took the theory from Pierre Bourdieu, namely social capital. In this study, to determine the informants, researchers used thetechnique Nonprobability Sampling which was selected by saturated sampling technique or census. In this technique the researcher takes the entire population to be a sample. This study contained 4 informants with the status of female prisoners who were at the Bagansiapiapi Detention Center. There are 3 convicts with drug cases and one convict with embezzlement of funds. The results of this study are, there are prisoners' relationships with their families that are still in good contact and some are not good, such as never visiting and calling. For daily activities, prisoners are only in the detention room, the lack of facilities causes a lack of activities to be carried out. by these inmates. The activities that are carried out are only general activities that are only carried out simultaneously with other residents, such as religious activities, morning exercise activities on weekends, and other activities on other big days. Female prisoners and detainees occupy the same room with a total of approximately 17 people with a room size of 4.6 x 6.5 meters. The high level of crime in the city of Bagansiapiapi has caused the Bagansiapiapi Detention Center to overcapacity where it should have accommodated 125 people to more than 700 people. Keywords: Female Prisoners, Bagansiapiapi Prison Branch